Schaum's quick guide to writing great research papers. - Rozakis, Laurie. 4 0 16; 5 (New York : McGraw-Hill, 1999)
A guide to writing a research paper that includes information on how to write a thesis statement, construct a logical paper, conduct online research, document sources, and avoid plagiarism.
Spine title: Writing great research papers.
Includes bibliographical references (p. 139-140) and index.
Keywords: 2 -- 0; 6; Report writing.;Research.;Report writing.;Research.; 20; 2